Decoding the neonatal chest radiograph: An insight into neonatal respiratory distress - Jain, Sanjay N; Modi, Tanvi; Varma, Ravi U (Indian Journal of Radiology and Imaging, 2020)
Respiratory distress is one of the leading causes of neonatal morbidity and mortality. Factors such as gestational age at birth, pulmonary maturity, and congenital factors are peculiar to this demographic. Clinical evaluation accompanied by chest radiography is the standard protocol for evaluating the underlying causative factors. Knowledge of the radiographic appearances of various pathologies and associations with certain congenital factors is quintessential for radiologists and primary neonatal care providers to steer the management in the right direction.
Keywords: Chest radiograph; congenital factors; gestational age; neonates; respiratory distress